The osteology of Shringasaurus indicus, an archosauromorph from the Middle Triassic Denwa Formation, Satpura Gondwana Basin, Central India. Issue 5 (30th March 2022) - Sengupta, Saradee; Bandyopadhyay, Saswati
ABSTRACT: Archosauromorpha originated in the middle–late Permian and started to diversify in both non-marine and marine ecosystems dominating the world by the Triassic. The evolution of this group is poorly documented because the fossil record is limited. A detailed osteological description of Shringasaurus indicus, a non-archosaurian archosauromorph, from the Middle Triassic Satpura Basin, Central India, is provided here. The collection includes cranial bones, namely the nasal, frontals with and without horns, postfrontal, parietal, maxilla, premaxilla, quadrate, vomer, dentary, and braincase. The collection also comprises postcranial bones such as cervical, dorsal, sacral and caudal vertebrae, and girdle and limb bones. The phylogenetic study incorporates the character states from cranial as well as postcranial elements of Shringasaurus indicus . Furthermore, Malerisaurus robinsonae, another non-archosaurian archosauromorph from India, has been included in the phylogenetic analysis. The analysis reveals that both Shringasaurus indicus and Malerisaurus robinsonae are azendohsaurid allokotosaurs and Shringasaurus indicus is the sister taxon to both the species of Azendohsaurus . The detailed description of Shringasaurus indicus elucidates that the animal had a pair of supraorbital horns, was a large herbivore, and has an incongruous mixture of basal archosauromorph and dinosaurian-like character-states. Hence, the present study helps to fill the gap, to a large extent, in understanding the nature of the morphological diversity of basal archosauromorphs after the Permian–Triassic mass extinction. SUPPLEMENTAL DATA–Supplemental materials are available for this article for free at www.tandfonline.com/UJVP